2006
DOI: 10.1016/j.tet.2006.03.033
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR assignments of the three dicyclopenta-fused pyrene congeners

Abstract: Complete 1 H and 13 C NMR assignments of the (di-)cyclopenta-fused pyrene congeners, cyclopenta[cd]-(2), dicyclopenta[cd, fg]-(3), dicyclopenta[cd,jk]-(4) and dicyclopenta[cd,mn]pyrene (5), respectively, are achieved using two-dimensional (2D) NMR spectroscopy. The experimental 13 C chemical shift assignments are compared with computed ab initio CTOCD-PZ2/6-31G** 13 C chemical shifts; a satisfactory agreement is found. Substituent-induced chemical shifts in the pyrene core induced by annelation of cyclopenta m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…157,158 However, it has been suggested that current density maps of the type calculated by Lazzeretti and co-workers [159][160][161][162][163][164][165] and Fowler and co-workers [166][167][168][169][170][171][172][173][174][175] give a more accurate description of electronic ring currents in aromatic systems than do NICS. The NICS calculated at the center of an aromatic ring has been suggested as a measure of aromaticity or antiaromaticity.…”
Section: Intermolecular Effectsmentioning
confidence: 99%
“…157,158 However, it has been suggested that current density maps of the type calculated by Lazzeretti and co-workers [159][160][161][162][163][164][165] and Fowler and co-workers [166][167][168][169][170][171][172][173][174][175] give a more accurate description of electronic ring currents in aromatic systems than do NICS. The NICS calculated at the center of an aromatic ring has been suggested as a measure of aromaticity or antiaromaticity.…”
Section: Intermolecular Effectsmentioning
confidence: 99%
“…Among them, the cyclopenta-fused pyrenes are an important class of CP-PAHs owing to their unique physical and photophysical properties, such as high electron affinities and anomalous fluorescence [17][18][19][20]. However, the reported synthetic methods towards the (di-)cyclopenta-fused pyrene congeners (i-iii, Scheme 1) have mainly been reliant on the flash vacuum pyrolysis of suitable precursors under harsh conditions (T ≥ 900 °C), which resulted in relatively low yields [ [21][22][23][24]. Palladium-catalyzed annulation has been recently proven as an efficient route to get access to aromatic hydrocarbons with peri-fused five-membered rings [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Fig. 2a, the peak signals at 8.30-7.80 ppm can be assigned to pyrene aromatic protons 32,33 and the peak signals at around 1.4 ppm should correspond to the methyl groups of Boc, 34 and the peak signal at 7.7 ppm should have resulted from the -ONH-group next to methylene. The 1 H NMR spectrum of pyrene-ONH 2 is shown in Fig.…”
mentioning
confidence: 98%